Ecoviability for ecosystem-based fisheries management - Doyen, Luc; Béné, Christophe; Bertignac, Michel; Blanchard, Fabian; Cissé, Abdoul Ahad; Dichmont, Catherine; Gourguet, Sophie; Guyader, Olivier; Hardy, Pierre-Yves; Jennings, Sarah; Little, Lorne Richard; Macher, Claire; et al. (Wiley, 2017)
Reconciling food security, economic development and biodiversity conservation is a key challenge, especially in the face of the demographic transition characterizing many countries in the world. Fisheries and marine ecosystems constitute a difficult application of this bio‐economic challenge. Many experts and scientists advocate an ecosystem approach to manage marine socio‐ecosystems for their sustainability and resilience. However, the ways by which to operationalize ecosystem‐based fisheries management (EBFM) remain poorly specified. We propose a specific methodological framework—viability modelling—to do so. We show how viability modelling can be applied using four contrasted case‐studies: two small‐scale fisheries in South America and Pacific and two larger‐scale fisheries in Europe and Australia. The four fisheries are analysed using the same modelling framework, structured around a set of common methods, indicators and scenarios. The calibrated models are dynamic, multispecies and multifleet and account for various sources of uncertainty. A multicriteria evaluation is used to assess the scenarios’ outcomes over a long time horizon with different constraints based on ecological, social and economic reference points. Results show to what extent the bio‐economic and ecosystem risks associated with the adoption of status quo strategies are relatively high and challenge the implementation of EBFM. In contrast, strategies called ecoviability or co‐viability strategies, that aim at satisfying the viability constraints, reduce significantly these ecological and economic risks and promote EBFM. The gains associated with those ecoviability strategies, however, decrease with the intensity of regulations imposed on these fisheries.